Association of pre-transplant erythropoiesis-stimulating agent responsiveness with post-transplant outcomes - Molnar, Miklos Z. (Oxford University Press, 2012)
BACKGROUND: The role of pre-transplant erythropoiesis-stimulating agent (ESA) responsiveness in affecting post-transplant outcomes is not clear. METHODS: Linking the 5-year patient data of a large dialysis organization to the ‘Scientific Registry of Transplant Recipients’, we identified 8795 hemodialyzed patients who underwent first kidney transplantation. Mortality or graft failure, delayed graft function (DGF) and acute rejection risks were estimated by Cox regression [hazard ratio (HR)] and logistic regression, respectively. RESULTS: Patients were 48 ± 14 years old and included 38% women and 36% diabetics. Compared to renal allograft recipients who were in the first quartile of pre-transplant ESA responsiveness index (ERI), i.e. ESA dose divided by hemoglobin and weight, recipients in second, third and fourth quartiles had higher adjusted graft-censored death HR (and 95% confidence intervals) of 1.7 (1.0–2.7), 1.8 (1.1–2.9) and 2.3 (1.4–3.9) and higher death-censored graft failure HR of 1.6 (1.0–2.5), 2.0 (1.2–3.1) and 1.6 (0.9–2.6), respectively. No significant association between pre-transplant ERI and post-transplant DGF or acute rejection was detected. CONCLUSIONS: Higher pre-transplant ERI during the hemodialysis treatment period was associated with worse post-transplant long-term outcomes including increased all-cause death and higher risk of graft failure.